Analisis Kebijakan Dana Desa Dalam Konsep Blue Economy Untuk Peningkatan Kesejahteraan Masyarakat Desa Di Sumatera Utara - Rangkuti, Shihabuddin Fuady; Sukardi, Sukardi; Syafii, M. (Owner : Riset dan Jurnal Akuntansi, 2024)
The Indonesia Sustainable Oceans program is to support Indonesia's change to a blue economy by advancing the financial, social and natural advantages got from sound beach front and sea biological systems. This study expects to complete an enlightening monetary examination of the improvement of the Town Cash strategy connected with the issue of executing the Blue Economy idea in North Sumatra Territory, Doing recognizable proof and assessment of the utilization of the Blue Economy idea in Langkat Rule and Focal Tapanuli Regime, North Sumatra Territory, Assessing the impact of the Social Strength Record, Financial Versatility File and Ecological Flexibility List fair and square of government assistance of town networks in the waterfront areas of Langkat Rule and Focal Tapanuli Rule, North Sumatra Territory. This study utilizes quantitative and subjective strategies to answer the current issue detailing. The consequences of this study are that the Coronavirus pandemic an affects steering approaches for utilizing Town Cash. Where, in 2023, the need utilization of Town Cash is focused on public monetary recuperation, public need projects, and alleviation for dealing with regular and non-cataclysmic events in supporting the accomplishment of the Town SDGs. At present there is no exceptional program that utilizes town cash to foster beach front regions or an extraordinary Blue Economy program in Focal Tapanuli locale and Langkat region. To some degree, the Social Flexibility File (IKS) variable impacts the Local area Government assistance variable, the Financial Versatility Record (IKE) variable affects the Local area Government assistance variable, the Natural Strength File (IKL) variable affects the variable Public government assistance. And that truly intends that in the event that the IKS, IKE, IKL factors progress, the degree of government assistance of the town local area additionally propels.